Shadowglass - Hayes, Erica (New York : St. Martin's Griffin, 2010)
Ice is a light-fingered fairy who can't resist a look at the powerful mirror. The mirror offers her a chance to achieve everything she's ever dreamed of. But when she pilfers it, she discovers that its power comes with a price: the mirror is a gateway to obsession and madness... and it will take every trick in her arsenal just to survive.
Formerly CIP.
Keywords: Fairies -- Fiction; Magic mirrors -- Fiction; Fantasy fiction